A Phenomenological Study of Undergraduate Students Experiences Using Artificial Intelligence Tools to Enhance Academic Writing Skills - Diana Septi Enggar Fananti; Tusino Tusino; Edi Sunjayanto Masykuri (FKIP - Universitas Riau, 2026)
This study explores undergraduate students’ experiences of using artificial intelligence (AI) writing tools to improve their academic writing skills. It was conducted in response to the growing adoption of AI in higher education and the persistent challenges students face in idea development, organization, grammar, vocabulary, and coherence. Using a qualitative phenomenological approach, the study involved eleven undergraduate students from an English Education Study Program who had experience with ChatGPT, Grammarly, and QuillBot. Data were collected through semi-structured interviews and field notes and analyzed using thematic analysis. The findings indicate that students used AI tools throughout the writing process, including brainstorming, outlining, drafting, revising, editing, and final refinement. Participants perceived AI as beneficial for generating ideas, improving language accuracy, organizing content, increasing writing efficiency, enhancing confidence, and reducing writing anxiety. However, several challenges emerged, including overdependence on AI, inaccurate or contextually inappropriate responses, unnatural language, prompt formulation difficulties, and platform limitations. Overall, the study concludes that AI writing tools can effectively support academic writing development when used critically, ethically, and responsibly. The findings highlight the need for pedagogical strategies and institutional guidelines that encourage the responsible integration of AI while strengthening students’ critical thinking, academic integrity, digital literacy, and independent writing skills.